Promising equipment for greenhouse wastewater treatment - Литвиненко, Олександр Анатолійович (Technology audit and production reserves, 2014)
The article presents the experimental results of greenhouse wastewater treatment by means of cavitation. It is noted that the use of ultrasonic cleaning has drawbacks. It is found that the use of hydrodynamic cavitation for wastewater treatment is a promising direction. It is noted that in effluents with residues of phenolic compounds, treatment is improved when using oxidizing agents such as hydrogen peroxide. A design of cavitation reactor for wastewater treatment using an ultrasonic radiation was proposed. The reactor was tested in an industrial environment and showed good treatment results. It was found that at simultaneous action of hydrodynamic cavitation and UV, the germicidal effect occurs. Due to this, pathogenic organisms are destructed. The article illustrates the experimental setup and cavitation reactor.